Cover Picture: Engineering Fast Ion Conduction and Selective Cation Channels for a High‐Rate and High‐Voltage Hybrid Aqueous Battery (Angew. Chem. Int. Ed. 24/2018). Issue 24 (3rd May 2018) - Liu, Chunyi; Wang, Xusheng; Deng, Wenjun; Li, Chang; Chen, Jitao; Xue, Mianqi; Li, Rui; Pan, Feng
Abstract : A hybrid aqueous battery based on two electrode materials with fast ion conduction and selective cation channels is reported by M. Xue, R. Li et al. in their Communication onpage 7046 ff. Using this strategy for integrating different electrode materials with unique cation selectivities towards metal ions a high‐voltage rechargeable aqueous battery is realized with a high capacity, remarkable energy density, and considerable capacity retention at high rate.